High Throughput mRNA Sequencing Reveals Potential Therapeutic Targets of Tao-Hong-Si-Wu Decoction in Experimental Middle Cerebral Artery Occlusion - Xianchun Duan; Xianchun Duan; Xianchun Duan; Lan Han; Lan Han; Daiyin Peng; Daiyin Peng; Weidong Chen; Weidong Chen; Can Peng; Can Peng; Ling Xiao; et al. (Frontiers Media S.A., 2019)
Background: Experimental and clinical studies have shown that Tao-Hong-Si-Wu decoction (THSWD) improved neurological deficits resulting from Middle Cerebral Artery Occlusion (MCAO). However, the mechanisms of action of THSWD in MCAO have not been characterized. In this study, the mRNA transcriptome was used to study various therapeutic targets of THSWD.Methods: RNA-seq was used to identify differentially expressed genes (DEGs). MCAO-induced up-regulated genes (MCAO vs. control) and THSWD-induced down-regulated genes (compared to MCAO) were identified. Intersection genes were defined as up-regulated differentially expression genes (up-DEGs) identified as MCAO-induced gene expression that were reversed by THSWD. Genes down-regulated by MCAO and up-regulated by THSWD were grouped as another series of intersections. Biological functions and signaling pathways were determined by gene ontology (GO) and Kyoto encyclopedia of genes and genomes (KEGG) pathway analyses. In addition, several identified genes were validated by RT-qPCR.Results: A total of 339 DEGs were filtered based on the 2 series (MCAO vs. control and MCAO vs. THSWD), and were represented by genes involved in cell cycle (rno04110), ECM-receptor interaction (rno04512), complement and coagulation cascades (rno04610), focal adhesion (rno04510), hematopoietic cell lineage (rno04640), neuroactive ligand-receptor interaction (rno04080), cocaine addiction (rno05030), amphetamine addiction (rno05031), nicotine addiction (rno05033), fat digestion and absorption (rno04975), glycerophospholipid metabolism (rno00564), and others. The protein-protein interaction (PPI) network consisted of 202 nodes and 1,700 connections, and identified two main modules by MOCDE.Conclusion: Cell cycle (rno04110), ECM-receptor interaction (rno04512), complement and coagulation cascades (rno04610), focal adhesion (rno04510), hematopoietic cell lineage (rno04640), and neuroactive ligand-receptor interactions (rno04080) are potential therapeutic targets of THSWD in MCAO. This study provided a theoretical basis for THSWD prevention of neurological deficits resulting from intracerebral hemorrhage.